Impact of birthweight on health-care utilization during early childhood - a birth cohort study - Mario Rüdiger; Luise Heinrich; Katrin Arnold; Diana Druschke; Jörg Reichert; Jochen Schmitt (BMC, 2019)
Abstract Background Comprehensive data are needed to evaluate the burden of low birthweight. Analysis of routine data on health-care utilization during early childhood were used to test the hypothesis that infants with low birthweight have (i) increased inpatient health-care utilization, (ii) higher hospital costs and (iii) different morbidity pattern in early childhood when compared with normal birthweight infants. Methods Children born between 2007 and 2013 that were insured at birth with the statutory health insurance AOK PLUS were included (N = 118,166, equaling 49% of the Saxon newborns) and classified into very low (< 1500 g, VLBW), low (1500-2499 g, LBW) birthweight and reference group (> 2500 g). Outcomes were: inpatient health-care utilization quantified by number and length of hospital stays; costs of hospitalizations including medication; reasons of hospitalizations for each year of life (YOL). Results 72, 38 and 22% of VLBW-, LBW- and reference group were hospitalized after perinatal period within the first YOL with a more than 5-fold increased risk in VLBW to be hospitalized for hemangioma, convulsions, hydrocephalus, hernia and respiratory problems. Median (IQR) cumulative cost of inpatient care during the first four YOLs was 2953 (1213-7885), 1331 (0-3451) and 0 (0-2062) Euro for respective groups. Inpatient early childhood health-care utilization (after first YOL) was higher in VLBW compared to healthy, normal birth weight infants (RR 3.92 [95%-CI 3.63, 4.23]), residents of rural areas (RR 1.37 [95%-CI 1.35, 1.40]) and in boys (RR 1.31 [95%-CI 1.29, 1.33]). Conclusion This large population-based birth-cohort study indicates a high clinical and economic burden of low birthweight which is not restricted to the first year of life.